Nurturing High Expectations: Living a Well-Lived Curriculum on a Humanistic Perspective - Budiraharjo, Markus (LLT Journal: A Journal on Language and Language Teaching, 2015)
This study reports an empirical investigation of the use of personal approach to integrating educational values in an English pre-service teacher education program. Using a Moodle-based Learning Management System called Exelsa, whichhas beeen in use in the past four years, each individual student received personalwritten responses from the instructor. Learning is perceived more as a journey todevelop self-knowledge that is not merely driven by instrumental orientations such asgrade-seeking mentality, rote memorization, and formalist-driven contents. A set ofanedoctal evidence suggested that highly personal notes addressed to each individualstudent brough significant change in the way each of them viewed himself or herselfin positive ways. When students felt highly appreciated as significant human beingsin the class, they were more likely to undergo learning more in a holistic manner. Ahumanistic philosophy of education necessitates such an approach to maintaininga relational trust among all class members. An instructor is supposedly skillful atnavigating the flows of class interactions, at times with unprecedented challenges. Arestropective study, this seeks to develop a better understanding as to whether suchan approach leaves a durable significance in their perspectives on learning.